Bioaktivitas Sediaan Gel Nanokoloid Perak Hasil Biosintesis Menggunakan Ekstrak Tanaman Keladi Sarawak (Alocasia macrorrhizos (L.)) Terhadap Bakteri Escherichia coli: Bioactivity of Silver Nanocolloid Gel Preparations Resulting from Biosynthesis Using Sarawak Caladium Plant Extract (Alocasia macrorrhizos (L.)) Against Escherichia coli Bacteria - Masykuroh, Athiah; Evani, Costa Rica (Akademi Farmasi Yarsi Pontianak, 2024)
Biological activity (bioactivity) test of silver nanocolloid gel biosynthesized by Alocasia macrorrhizos (L.) plant extract and AgNO3 solutions against Escherichia coli bacteria has been conducted. The gel preparation was made with silver nanocolloids as an active ingredient. The AgNO3 solution used at biosynthesis process was made in 3 concentration variations : 0.05 (F1); 0.10 (F2) and 0.15 M (F3). Antibacterial activity test was conducted by paper disc diffusion method. The measuring results was diameter of the clear zone formed around the paper disc : 11.90 mm (F1), 12.67 mm (F2) and 13.13 mm (F3) with a positive control of neomycin sulfate gel of 23.16 mm. Based on these results, it can be concluded that the silver nanocolloid gel has inhibitory power against Escherichia coli bacteria with strong category for all variations.